From native to cross-platform hybrid development : CodeGT, design and development of a mobile app for ERP - Pinto, Carlos Manuel Manso (2018)
The current trend towards mobility of individuals, together with the exponential growth of the number of mobile devices led the market to a boom in the demand for the development of mobile applications. Moreover, with the expansion and heterogeneity of the mobile devices and platforms, software companies need to search for faster and cheaper ways to develop applications that can span as many devices as possible to capture the market. Currently, the Android and iOS Operating Systems roughly share and dominate the mobile market, with timid expressions of other competitors. Each of these mobile operating systems were developed using their own languages, strategy and SDKs for development of applications using their libraries – known as Native apps. On the other hand, the evolution of HTML5, CSS and JavaScript created generic alternatives to create mobile apps that run on devices on all operating systems, although lacking the capability to access the device’s full potential. Alongside came the new Hybrid cross-platform development frameworks, which try to take the best of both worlds. This dissertation describes the evolution of the different mobile app development approaches and the state-of-the-art in their development techniques, and compares them with the Hybrid app approach, then highlighting the trends in mobile app development using Hybrid platforms and their advantages. This research includes the development of a mobile Hybrid application, CodeGT, which interacts with an Enterprise Resource Planning (ERP) to access the Transport Documents registered in this ERP and access to the code transmitted by the Portuguese Tax Authority (AT), therefore not requiring the printing of documents and meeting a need of the business market. This application does already have customer industry companies interested in it.